Reducing scratching behavior in atopic dermatitis patients using the EMDR treatment protocol for urge: A pilot study - de Veer, Mathijs R.; Waalboer-Spuij, Rick; Hijnen, Dirk Jan; Doeksen, Do; Busschbach, Jan J.; Kranenburg, Leonieke W. (Frontiers in Medicine, 2023)
Background Itch, and thereby the scratching behavior, is a common complaint in atopic dermatitis. Scratching damages the skin, which in turn worsens the itch. This itch-scratch cycle perpetuates the skin condition and has a major impact on the patient's quality of life. In addition to pharmacological treatment, psychological interventions show promising results in reducing scratching behavior. Objectives To investigate the effect of treatment according the EMDR treatment protocol for urge on scratching behavior of atopic dermatitis patients in a controlled study. Methods This study applies a multiple baseline across subjects design. Six patients were randomly allocated to different baseline lengths and all of them started registration of scratching behavior at the same day, using a mobile phone application. Nocturnal scratching was registered by a smart watch application. The total study duration was 46 days and was equal for all patients. Treatment consisted of two sessions using the EMDR treatment protocol for urge. Furthermore, standardized measures were used to assess disease activity, quality of life, and self-control. The nonoverlap of all pairs effect size was calculated for the daily measure data. Results One patient dropped out. Visual inspection suggests that the scratching behavior decreased over time in all patients. Furthermore, a moderate effect size of the treatment is found. During the baseline phase, scratching behavior fluctuated considerably and showed a slight negative trend. Outcomes of disease activity decreased over time and patients' self-control and quality of life improved after treatment. Nocturnal scratching behavior did not change after the intervention. Conclusion The results of the visual analysis of day time scratching behavior, disease activity, quality of life, and self-control seem promising. These findings pave the way for future research into the effect of the new intervention on other skin conditions suffering from scratching behavior, such as prurigo nodularis.